Lehigh Conference on Plastic Design of Multi-Story Frames-A Summary - Driscoll, Jr. (Engineering Journal, 1966)
In August, 1965, a conference of teachers of structural engineering and practicing structural engineers was held at Lehigh University. The purpose of the conference was to present a comprehensive coverage of new developments in the application of plastic design principles to the design of steel multi-story building frames. The conference consisted of a group of basic lectures and experimental tests performed by members of the Lehigh staff and additional supplemental lectures by outstanding engineers and educators who were attending the conference.